The answer is 8 and 13
<span>
y = ax + b
y = 4, x = 1 </span>⇒ 4 = a + b
y = 6, x = 3 ⇒ 6 = 3a + b
Solve the system of equation:
a + b = 4
3a + b = 6
______
b = 4 - a
3a + b = 6
______
3a + 4 - a = 6
2a + 4 = 6
2a = 6 - 4
2a = 2
a = 2/2 = 1
b = 4 - a = 4 - 1 = 3
So, the function rule is: y = x + 3
Thus, if x = 7, then y = 7 + 3 = 10
If x = 10, then y = 10 + 3 = 13
x y
1 4
3 6
4 7
5 8
7 10
10 13
Answer:
Can't see the picture because old computer but isn't 16 minus 17 = -1 (negative 1)
Step-by-step explanation:
Answer:
EK = 9
Step-by-step explanation:
x + 11 = -5 + 2x -5 + 2x
x+11 = -10 + 4x
11 = 3x - 10
3x = 21
x = 7
EK =-5 + 2 × 7
EK = 14 - 5
EK = 9
Answer:
c=45
Step-by-step explanation:
36^2+27^2=c2
1296+729=c2
2095=c2
Then square root it to get
c=45
Answer:
a number to another number
Step-by-step explanation:
One number in comparison to another number
for example 3/4=4/5x